A piece of cake : a memoir - Brown, Cupcake (New York [etc.] Bantam Books, 2006)
'A Piece of Cake' is the story of a girl named Cupcake, which begins when, aged 11, she is orphaned and placed in the care of sadistic foster parents. Neglected and sexually abused she fell into drug abuse and gang culture before turning her life around
Keywords: Brown, Cupcake -- Biografía